2021
DOI: 10.3389/fonc.2021.662954
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Recall Pneumonitis After Treatment With Checkpoint Blockade Immunotherapy: A Case Series and Review of Literature

Abstract: BackgroundRadiation recall pneumonitis (RRP) is a poorly understood clinical syndrome in which patients develop radiation pneumonitis triggered by a systemic agent, often years after the completion of radiation therapy. Immune checkpoint blockade agents have only recently been posited as a trigger for RRP. Here, we present three cases of immunotherapy-induced RRP.Case PresentationOur first patient was diagnosed with primary lung adenocarcinoma, and 4.5 years after completing radiation therapy developed symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…ICIs enhance the local immune response in lung parenchyma, promoting inflammation in previously injured areas, thus triggering RRP [ 28 ]. RT promotes inflammation in the lung parenchyma through several mechanisms ( Figure 2 ) [ 29 ]. A case series suggested that RRP might be associated with IIP, as in the case we are presenting [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICIs enhance the local immune response in lung parenchyma, promoting inflammation in previously injured areas, thus triggering RRP [ 28 ]. RT promotes inflammation in the lung parenchyma through several mechanisms ( Figure 2 ) [ 29 ]. A case series suggested that RRP might be associated with IIP, as in the case we are presenting [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, withdrawal of the suspected triggering drug is recommended [ 23 ]. In some case reports of ICI-triggered RRP, ICI treatment was resumed following the resolution of the RRP, and no toxicity recurrences were reported [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation recall, on the other hand, is the reactivation of the damage at the level of the previously treated site, at a distance of several times from the radiotherapy treatment, following the administration of a drug. The phenomenon can occur following the administration of chemotherapy [ 40 , 41 ], target therapy [ 42 , 43 ], immunotherapies [ 44 , 45 ] or vaccinations [ 46 , 47 ], and it is not radiation dose-related. Radiation recall reactions were first described in 1959 by D’Angio et al who described the onset of dermatitis in patients treated with actinomycin D, after having previously undergone radiotherapy treatments, demonstrating the absence of such reactions after only treatment with actinomycin and the significant increase of the same in patients treated with the combination of actinomycin and radiotherapy compared to those treated exclusively with radiotherapy [ 48 ].…”
Section: Mechanisms Of Lung Radiation Damagementioning
confidence: 99%
“…53 Other rare toxicities including the radiation recall phenomenon can occur in all patients receiving systemic therapies including immunotherapy. 54 Typically the most common type of recall reaction after thoracic treatment is radiation pneumonitis, although rare conditions such as recall myelopathy may also occur. 16 The use of RT in patients who have received surgical management has recently been explored in the lung ART trial in which patients with resected stage III lung cancer were randomized to receive postoperative RT or observation.…”
Section: Multimodality Therapiesmentioning
confidence: 99%